Proses Produksi Pesan Media Sosial WhatsApp Terhadap Eksistensi Diri Dan Solidaritas Pengguna - RIYODINA PRATIKTO; Kholil; Titi Widaningsih; Jamalullail (Widya Duta: Jurnal Ilmiah Ilmu Sosial Budaya, 2023)
Advances in technology, especially communication technology is very fast. One of them is the presence of new media, in the form of online media and social media, which has an impact on changing the way of communicating in society. This research was conducted with the aim of knowing the message production process for social media users, especially WhatsApp (WA), by using trait/character theory, conversational narcissism, argumentativeness, and social & communicative anxiety. This study uses the constructivism paradigm. This research uses a qualitative approach, and case study methods, primary and secondary data sources. The data were obtained through observing active members of one of the WA groups, while interviews were conducted with the WAG 'pak lurah', and 5 members of the ikasma3bdg'82 board, as well as through a literature study. The results of the research show that a person's character can be reflected through the messages they produce. Messages produced primarily by WAG users produce the self-existent nature of WAG users. This can be seen from the character who always emphasizes his abilities, always wants to dominate the conversation, and so on. The second feature that emerges from the message production process is the nature of solidarity possessed by WAG users. So that the nature of this solidarity is able to maintain harmony among fellow WAG users. Keywords: Message production, User characteristics, WAG